Successional stage, fragmentation and exposure to extraction influence the population structure of Euterpe precatoria (Arecaeae) - Gerardo Avalos; Mauricio Fernández Otárola; James Theodore Engeln (Revista de Biología Tropical, 2013)
The neotropical palm Euterpe precatoria is subject to extraction for its valuable palm heart. The development of management and conservation practices for this species requires understanding of its population structure, dynamics, and traditional use across the range of environments it inhabits, from different successional stages in continuous forest to forest fragments. Here, we analyzed how the population structure of E. precatoria varies with successional stage, fragmentation, and exposure to extraction. Since E. precatoria recruitment increases with disturbance, we expected seedling density to be higher in secondary forests and fragments relative to primary forests. The study was conducted from 2007-2008 in the Caribbean Slope of Costa Rica at Braulio Carrillo National Park (BCNP), La Selva Biological Station (LSBS), Manú Center, and Finca El Progreso (FEP). The first two sites had continuous primary and secondary forests (BCNP had one extracted primary forest); the last two consisted of primary forest fragments. Population structure was variable, with greater densities in the extracted primary forest, and in the secondary forests, as compared to primary forests and fragments. Palms <5m across all sites represented 50-90% of the total number of individuals. In sites that suffered historical over-extraction, local communities have lost the tradition of consuming this species. Understanding how population dynamics is affected by extraction and succession is essential to the design of sustainable management programs rooted in community participation.